COMPARATIVE STUDY OF SAFETY FACTOR AND STRENGTH FACTOR IN NUMERICAL MODELING FOR SLOPE STABILITY ANALYSIS BASED ON THE HOEK-BROWN CRITERION - Yacob
Slope stability is one of the crucial factors that must be considered when designing a slope in an open pit mine. The Safety Factor (FoS) is a common indicator used to evaluate slope stability. However, in some numerical modelling software using the FEM method, the term Strength Factor (SF) is used to determine the slope strength at specific points. Therefore, this research aims to compare FoS and SF in slope stability analysis using numerical modelling based on the Hoek-Brown criterion. The research findings indicate a significant difference between the values of FoS and SF in determining slope stability. This comparison provides insights into the reliability of each indicator in depicting the actual stability condition of the slope. These findings are expected to contribute to developing more accurate and reliable analysis methods for slope stability.